Meningkatkan Integritas Sebagai Mahasiswa Merupakan Implementasi Wujud Bela Negara - Irwan Triadi; Akhfa Kamilla Sulaeman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal discusses the concept and implementation of state defense in the context of student life. State defense is an important concept to strengthen and protect the country's sovereignty, as well as build awareness and a sense of national responsibility towards their country. This journal focuses on the conceptual framework of state defense, including the values contained in the concept. Values such as patriotism, loyalty to the country, concern for the environment, and a sense of social responsibility are crucial in building a strong sense of state defense in university students. Furthermore, this journal analyzes how state defense can be implemented in everyday life as a student. The research method used is qualitative description, while the type of research is library research, the activity is carried out by collecting data related to the title which is literature. Through good civic education, active participation in social and political activities, and real contributions to state development. In addition, this journal also discusses how improving integrity as a student is an implementation of state defense and also the reasons why improving integrity and state defense are very important. The author suggests several ways that can be done to improve integrity as a student to realize state defense and citizenship in universities, expand community participation programs, and build awareness of the importance of state defense through mass media and social campaigns. This journal summarizes the importance of state defense in building and protecting state defense, and provides a framework that can be used by educational institutions in implementing the concept of state defense. It is hoped that readers of this journal will gain a better understanding of state defense and the importance of building state defense awareness.